Assessment of photovoltaic efficacy in antimony-based cesium halide perovskite utilizing transition metal chalcogenide - Alghafis, Abdullah; Sobayel, K. (International Journal of Renewable Energy Development, 2024)
Antimony-based perovskites have been recognized for their distinctive optoelectronic attributes, standard fabrication methodologies, reduced toxicity, and enhanced stability. The objective of this study is to systematically investigate and enhance the performance of all-inorganic solar cell architectures by integrating Cs3Sb2I9, a perovskite-analogous material, with WS2—a promising transition metal dichalcogenide—used as the electron transport layer (ETL), and Cu2O serving as the hole transport layer (HTL). This comprehensive assessment extends beyond the mere characterization of material attributes such as layer thickness, doping levels, and defect densities, to include a thorough investigation of interfacial defect effects within the structure. Optimal efficiency was observed when the Cs3Sb2I9 absorber layer thickness was maintained within the 600-700 nm range. The defect tolerance for the absorber layer was identified at 1×1015/cm3, with the ETL and HTL layers exhibiting significant defect tolerance at 1×1016/cm3 and 1×1017/cm3, respectively. Furthermore, this study calculated the minority carrier lifetime and diffusion length, establishing a strong correlation with defect density; a minority carrier lifetime of approximately 1 µs was noted for a defect density of1×1014/cm3 in the absorber layer. A noteworthy finding pertains to the balance between the high work function of the back contact and the incorporation of p-type back surface field layers, revealing that interposing a highly doped p+ layer between the Cu2O and the metal back contact can elevate the efficiency to 21.60%. This approach also provides the freedom to select metals with lower work functions, offering a cost-effective advantage for commercial-scale applications.